2021
DOI: 10.1111/andr.12990
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic benefits with adherence to testosterone therapy in men with hypogonadism and type 2 diabetes mellitus

Abstract: Background:While previous studies have demonstrated testosterone's beneficial effects on glycemic control in men with hypogonadism and Type 2 Diabetes, the extent to which these improvements are observed based on the degree of treatment adherence has been unclear.Objectives: To evaluate the effects of long-term testosterone therapy in A1C levels in men with Type 2 Diabetes Mellitus and hypogonadism, controlling for BMI, pretreatment A1C, and age among different testosterone therapy adherence groups. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…showed that T replacement results in improvement in insulin resistance and glycemic control in all men including those with T2D ( 14 ). A few other RCTs ( 11 , 37 , 38 ) and retrospective studies ( 39 41 ) have shown similar results. Moreover, the data from testosterone trials showed that benefits of T therapy on insulin resistance and fasting glucose extend to men in the elderly age group ( 42 ).…”
Section: Discussionmentioning
confidence: 53%
“…showed that T replacement results in improvement in insulin resistance and glycemic control in all men including those with T2D ( 14 ). A few other RCTs ( 11 , 37 , 38 ) and retrospective studies ( 39 41 ) have shown similar results. Moreover, the data from testosterone trials showed that benefits of T therapy on insulin resistance and fasting glucose extend to men in the elderly age group ( 42 ).…”
Section: Discussionmentioning
confidence: 53%